FcγRII-binding Centyrins mediate agonism and antibody-dependent cellular phagocytosis when fused to an anti-OX40 antibody. Issue 3 (3rd April 2018) - Zhang, Di; Whitaker, Brian; Derebe, Mehabaw G.; Chiu, Mark L.
ABSTRACT: Immunostimulatory antibodies against the tumor necrosis factor receptors (TNFR) are emerging as promising cancer immunotherapies. The agonism activity of such antibodies depends on crosslinking to Fc gamma RIIB receptor (FcγRIIB) to enable the antibody multimerization that drives TNFR activation. Previously, Fc engineering was used to enhance the binding of such antibodies to Fcγ receptors. Here, we report the identification of Centyrins as alternative scaffold proteins with binding affinities to homologous FcγRIIB and FcγRIIA, but not to other types of Fcγ receptors. One Centyrin, S29, was engineered at distinct positions of an anti-OX40 SF2 antibody to generate bispecific and tetravalent molecules named as mAbtyrins. Regardless of the position of S29 on the SF2 antibody, SF2-S29 mAbtyrins could bind FcγRIIB and FcγRIIA specifically while maintaining binding to OX40 receptors. In a NFκB reporter assay, attachment of S29 Centyrin molecules at the C-termini, but not the N-termini, resulted in SF2 antibodies with increased agonism owing to FcγRIIB crosslinking. The mAbtyrins also showed agonism in T-cell activation assays with immobilized FcγRIIB and FcγRIIA, but this activity was confined to mAbtyrins with S29 specifically at the C-termini of antibody heavy chains. Furthermore, regardless of the position of the molecule, S29 Centyrin could equip an otherwise Fc-silent antibody with antibody-dependent cellular phagocytosis activity without affecting the antibody's intrinsic antibody-dependent cell-meditated cytotoxicity and complement-dependent cytotoxicity. In summary, the appropriate adoption FcγRII-binding Centyrins as functional modules represents a novel strategy to engineer therapeutic antibodies with improved functionalities.